Enediyne Anticancer Antibiotic Lidamycin: Chemistry, Biology and Pharmacology - Shao, Rong-guang; Zhen, Yong-su (Anti-Cancer Agents in Medicinal Chemistry, 2008)
The enediyne antibiotics, the potent anticancer agents that contain diyne-ene functional groups, are appreciated for their novel molecular architecture, their remarkable biological activity and their fascinating mechanism of action. Their anticancer activity is apparently due to their ability to damage DNA through radical-mediated hydrogen abstraction. The enediyne antibiotics show markedly cytotoxicities against cancers in vitro and in vivo. Lidamycin is a member of the enediyne anticancer antibiotic family. This review examines lidamycin with particular emphasis on the discovery, the biological properties and its structure-activity relationships. In addition, the possible mechanisms of action of lidamycin are described. Recent progress, particularly in the areas of biosynthesis, and immunoconjugates are highlighted. Finally, the pharmacological applications of lidamycin in cancer therapy and its potential use as anticancer agents are also discussed.
Keywords: DNA damage